2020
DOI: 10.1159/000506928
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatic Angiosarcoma: A Rare Liver Malignancy – Varying Manifestations but Grave Prognosis

Abstract: Primary hepatic angiosarcoma (PHA) is a rare mesenchymal liver tumor, accounting for 0.1-2% of primary liver malignancies. The clinical presentations of PHA are variable, from asymptomatic to liver failure or complicated with tumor rupture. The diagnosis of PHA is difficult due to the lack of specific clinical manifestation and investigation results, which can be confused with other liver tumors resulting in late diagnosis. However, there is currently a paucity of effective therapeutic approaches. We advocate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Acute intra-abdominal bleeding may occur secondary to the spontaneous rupture of PHA, as previously described by a few case reports [ 9 , [14] , [15] , [16] ]. Haemoperitoneum due to spontaneous tumour rupture occurs in 15–27% of PHA cases and DIC may develop subsequently [ 2 ].…”
Section: Clinical Discussionmentioning
confidence: 96%
“…Acute intra-abdominal bleeding may occur secondary to the spontaneous rupture of PHA, as previously described by a few case reports [ 9 , [14] , [15] , [16] ]. Haemoperitoneum due to spontaneous tumour rupture occurs in 15–27% of PHA cases and DIC may develop subsequently [ 2 ].…”
Section: Clinical Discussionmentioning
confidence: 96%
“…In 2020, Rujeerapaiboon et al reported that, out of 3 female cases with liver angiosarcoma, one presented with abdominal pain and weight loss. 8 The abdominal CT scan detected diffused multiple arterial enhancing infiltrating nodules varying in size, scattered throughout the entire liver. Laparoscopic liver biopsy confirmed liver angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is difficult due to the non‐specific nature of symptoms. It is associated with a poor survival due to its rapid progression, high recurrence rate and resistance to many traditional chemotherapy and radiotherapy options (1).…”
Section: Figmentioning
confidence: 99%